Conflict (work-family and family-work) and task performance: The role of well-being in this relationship - Ana Moreira; Tiago Encarnaç\~ao; Jo\~ao Viseu; Manuel Au-Yong-Oliveira (Administrative Sciences, 2023)
Recent societal changes have brought new challenges to contemporary organisations, e.g., how to properly manage the work-family/family-work dyad and, thus, promote adequate task performance. This paper aimed to study the relationship between conflict (work-family and family-work) and task performance, and whether this relationship was moderated by well-being. Thus, the following hypotheses were formulated: (1) conflict (work-family and family-work) is negatively associated with task performance; (2) conflict (work-family and family-work) is negatively associated with well-being; (3) well-being is positively associated with task performance; and (4) well-being moderates the relationship between conflict (work-family and family-work) and task performance. A total of 596 subjects participated in this study, all employed in Portuguese organisations. The results underlined that only family-work conflict was negatively and significantly associated with task performance. Work-family conflict established a negative and significant relationship with well-being. Well-being was positively and significantly associated with performance and moderated the relationship between conflict (work-family and family-work) and task performance. These results show that organisations should provide employees with situations that promote their well-being, especially in Portugal, where a relationship culture exists (rather than task culture, which is predominant in the USA and Canada, for example) which means that additional and considerable time must be dedicated to personal and family matters for people to fit in and be accepted harmoniously.
Keywords: 350; family-work conflict; performance; well-being; work-family conflict